2018
DOI: 10.1177/2309499018760112
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid levels of TWEAK and matrix metalloproteinase 1 in patients with osteoarthritis, and associations with disease severity

Abstract: The concentration of TWEAK and MMP-1 in the synovial fluid were relatively high in the early stage of OA, and the levels decreased as the OA progressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…MMPs are expressed in several different types of cells and have important roles in diverse cellular processes (Araki & Mimura, 2017), including the degradation of different components of the extracellular matrix (Amar, Smith, & Fields, 2017). Among all MMPs, MMP-1 has been reported to be upregulated in OA patients (Amar et al, 2017;Hwang et al, 2018), implying that anti-MMP-1 antibody is a promising new strategy for treatment of OA. In the current study, the GEO database confirmed higher levels of MMP-1 expression in OA tissue compared with those in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are expressed in several different types of cells and have important roles in diverse cellular processes (Araki & Mimura, 2017), including the degradation of different components of the extracellular matrix (Amar, Smith, & Fields, 2017). Among all MMPs, MMP-1 has been reported to be upregulated in OA patients (Amar et al, 2017;Hwang et al, 2018), implying that anti-MMP-1 antibody is a promising new strategy for treatment of OA. In the current study, the GEO database confirmed higher levels of MMP-1 expression in OA tissue compared with those in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined other and less commonly measured inflammatory markers, such as serum APRIL, BAFF, TWEAK, sCD30, sCD163, and CHI3L1; these have important immunological functions and have been implicated in autoimmune diseases and in chondrocyte dysfunction underlying OA. 84445 While most of these markers have not been examined in clinical studies following administration of foods or nutraceuticals, and no effects were noted in our study, markers such as sCD30 has been reported to be altered by nutritional deficiencies in children. 46…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have reported that the pathological erosion of the articular cartilage during TMJ‐OA mainly results from the imbalance between chondrocyte‐regulated MMP activities (Zhang et al., 2016). In this inflammatory context, articular chondrocytes express higher levels of MMP‐1 (Hwang et al., 2018), which can degrade collagen types I, II, and III (Heard et al., 2012), causing fibrinolytic remodeling of soft tissue structures and loss of articular cartilage in TMJ‐OA (Souza, Lovato da Silva, Nasser, Fedorowicz, & Al‐Muharraqi, 2012). Moreover, the overexpression of MMP‐1 detected in the synovial fluid has been associated with TMJ‐OA progression (Luo et al., 2015; Srinivas et al., 2001), and similarly, the augmented expression of MMP‐13 in retrodiscal tissues has been related to extensive internal derangement in TMJ‐OA (Gho, Choi, Park, & Huh, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, pro‐inflammatory cytokine contribution during TMJ‐OA pathogenesis has also been investigated (Hwang et al., 2018; Kaneyama, Segami, Sun, Sato, & Fujimura, 2005; Kubota et al., 1998; Vernal et al., 2008). Several studies have reported that the overexpression of TNF‐α induces the activation of MMPs in the synovium and, consequently, the inflammation‐mediated degradation of articular tissues in TMJ‐OA and rheumatoid arthritis (Hou et al., 2001; Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%